Prognostic Relevance of Subjective Theories of Illness on the Clinical and Psychological Parameters in Irritable Bowel Syndrome Patients – A Longitudinal Study - Riedl, A.; Maass, J.; Ahnis, A.; Stengel, A.; Mönnikes, H.; Klapp, B.F.; Fliege, H. (IntechOpen, 2012)
None